2005
DOI: 10.1007/s10695-005-5288-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Hypoxia in Trout (Oncorhynchus mykiss) on Immature Erythrocyte Release and Production of Oxidative Radicals

Abstract: This paper evaluates the response of trout exposed to acute hypoxia between 8.7 mgO 2 /l (controls) and 1.4 mgO 2 /l. Temperature, pH, NH4, oxygen consumption rate and spleen-somatic index (SSI) were evaluated. Blood cell counts, oxidative radicals (ORs) production and immature erythrocytes were assessed to evaluate their relationship with the degree of hypoxia. Acute hypoxia induced a decrease in water pH (p<0.05), oxygen consumption rate (60% less), SSI (55% less) and a significant increase of water ammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The head kidney is the main erythropoietic organ of teleosts, and its cellular composition resembles mammalian bone marrow, while the spleen shows a weak erythropoietic activity (Fange 1994) and acts mainly as a blood reservoir supplying erythrocytes to the circulation in case of increased O 2 demand (Yamamoto, Itazawa, and Kobayashi 1980;Yamamoto 1987;Valenzuela et al 2005).…”
Section: Erythropoiesismentioning
confidence: 99%
“…The head kidney is the main erythropoietic organ of teleosts, and its cellular composition resembles mammalian bone marrow, while the spleen shows a weak erythropoietic activity (Fange 1994) and acts mainly as a blood reservoir supplying erythrocytes to the circulation in case of increased O 2 demand (Yamamoto, Itazawa, and Kobayashi 1980;Yamamoto 1987;Valenzuela et al 2005).…”
Section: Erythropoiesismentioning
confidence: 99%
“…Therefore, at least in this animal model, 20 min is the minimum incubation time for the mixture blood/NBT. It is shorter than that reported in the literature to evaluate the "respiratory burst" which is usually 45 min (Valenzuela et al 2005) or 60 min (Secombes 1990;Logambal et al 2000;Puangkaew et al 2004). This 20 min incubation time is even shorter than that of 30 min used by other authors (Anderson and Siwicki 1993;Kumari and Sahoo 2006;Ispir et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Formazan produced by NBT reduction mediated by ROS has traditionally been measured after 30 (Anderson and Siwicki 1993;Kumari and Sahoo 2006;Ispir et al 2008), 45 (Valenzuela et al 2005) or 60 min incubation (Secombes 1990;Logambal et al 2000;Puangkaew et al 2004), but we have not been able to find justification for the incubation time used. Therefore, study of formazan formation kinetics was necessary to determine the optimal incubation time.…”
mentioning
confidence: 76%
“…Furthermore, when acclimated to hypoxia, haematocrit increased in fish from the swamp population, but not in fish from the lake population. Interspecific differences in the haematological responses to hypoxia have been previously noted in fishes (Wood and Johansen 1973;Lykkeboe and Weber 1978;Jensen et al 1993;Valenzuela et al 2005). In addition several studies have reported changes in haematological traits in response to hypoxia acclimation within species (Yamamoto et al 1983; Note: Fish (F 1 s) from the two sites were reared under normoxic conditions and acclimated for 4 weeks to normoxia and hypoxia at 26 8C.…”
Section: Discussionmentioning
confidence: 99%